Anatomy of Echinodorus (Alismataceae) scapes from northeastern Brazil as applied to taxonomy - Matias, L. Q.; Soares, A.; Scatena, V. L. [UNESP] (Royal Botanic Garden Edinburgh, 2008)
The anatomical characters of the scape of Echinodorus glandulosus, E. lanceolatus, E. palaefolius, E. paniculatus, E. pubescens and E. subalatus subsp. subalatus (Alismataceae) were examined. These six sympatric species occur in northeastern Brazil and demonstrate great morphological similarity. The aim of the present study was to identify anatomical characters of taxonomic importance. Scapes possess a uniseriate epidermis composed of thin-walled tabular cells. The scapes of most species have differentiated epidermis, cortex, and vascular cylinders. There are several layers of regular chlorenchyma cells immediately below the epidermis, intercalated with collateral vascular bundles, in all species. There are also laticiferous ducts throughout the scape, and aerenchyma in both the cortex and pith. The shape and outline of scapes, the presence and position of winged extensions, the absence of differentiated vascular cylinders or cortex, and the number of vascular bundles are important characters for differentiating species in Echinodorus. An identification key employing the features analysed is provided. © 2008 Trustees of the Royal Botanic Garden.
Keywords: Alismataceae; Aquatic plants; Echinodorus; Scape anatomy